Casein Kinase 1 and Human Disease: Insights From the Circadian Phosphoswitch - Francisco, Joel C.; Virshup, David M. (Frontiers in Molecular Biosciences, 2022)
Biological systems operate in constant communication through shared components and feedback from changes in the environment. Casein kinase 1 (CK1) is a family of protein kinases that functions in diverse biological pathways and its regulation is beginning to be understood. The several isoforms of CK1 take part in key steps of processes including protein translation, cell-cell interactions, synaptic dopaminergic signaling and circadian rhythms. While CK1 mutations are rarely the primary drivers of disease, the kinases are often found to play an accessory role in metabolic disorders and cancers. In these settings, the dysregulation of CK1 coincides with increased disease severity. Among kinases, CK1 is unique in that its substrate specificity changes dramatically with its own phosphorylation state. Understanding the process that governs CK1 substrate selection is thus useful in identifying its role in various ailments. An illustrative example is the PERIOD2 (PER2) phosphoswitch, where CK1δ/ε kinase activity can be varied between three different substrate motifs to regulate the circadian clock.